Molecular Design, Synthesis and Trypanocidal Activity of Dipeptidyl Nitriles as Cruzain Inhibitors. - Leandro A A Avelar; Cristian D Camilo; Sérgio de Albuquerque; William B Fernandes; Cristiana Gonçalez; Peter W Kenny; Andrei Leitão; James H McKerrow; Carlos A Montanari; Erika V Meñaca Orozco; Jean F R Ribeiro; Josmar R Rocha; et al. (Public Library of Science (PLoS), 2015)
A series of compounds based on the dipeptidyl nitrile scaffold were synthesized and assayed for their inhibitory activity against the T. cruzi cysteine protease cruzain. Structure activity relationships (SARs) were established using three, eleven and twelve variations respectively at the P1, P2 and P3 positions. A Ki value of 16 nM was observed for the most potent of these inhibitors which reflects a degree of non-additivity in the SAR. An X-ray crystal structure was determined for the ligand-protein complex for the structural prototype for the series. Twenty three inhibitors were also evaluated for their anti-trypanosomal effects and an EC50 value of 28 μM was observed for the most potent of these. Although there remains scope for further optimization, the knowledge gained from this study is also transferable to the design of cruzain inhibitors based on warheads other than nitrile as well as alternative scaffolds.